Adipose-Derived Stem Cells Ameliorate Allergic Airway Inflammation by Inducing Regulatory T Cells in a Mouse Model of Asthma. (26th August 2014) - Cho, Kyu-Sup; Park, Mi-Kyung; Kang, Shin-Ae; Park, Hee-Young; Hong, Sung-Lyong; Park, Hye-Kyung; Yu, Hak-Sun; Roh, Hwan-Jung
Abstract : Although several studies have demonstrated that mesenchymal stem cells derived from adipose tissue (ASCs) can ameliorate allergic airway inflammation, the immunomodulatory mechanism of ASCs remains unclear. In this study, we investigated whether regulatory T cells (Tregs) induction is a potential mechanism in immunomodulatory effects of ASCs on allergic airway disease and how these induced Tregs orchestrate allergic inflammation. Intravenous administration of ASCs significantly reduced allergic symptoms and inhibited eosinophilic inflammation. Airway hyperresponsiveness, total immune cell and eosinophils in the bronchoalveolar lavage fluid, mucus production, and serum allergen-specific IgE and IgG1 were significantly reduced after ASCs administration. ASCs significantly inhibited Th2 cytokines (IL-4, IL-5, and IL-13) and enhanced Th1 cytokine (IFN- γ ) and regulatory cytokines (IL-10 and TGF- β ) in the bronchoalveolar lavage fluid and lung draining lymph nodes. Furthermore, levels of IDO, TGF- β, and PGE2 were significantly increased after ASCs administration. Interestingly, this upregulation was accompanied by increased Treg populations. In conclusion, ASCs ameliorated allergic airway inflammation and improved lung function through the induction of Treg expansion. The induction of Treg by ASCs involves the secretion of soluble factors such as IDO, TGF- β, and PGE2 and Treg might be involved in the downregulation of Th2 cytokines and upregulation of Th1 cytokines production.